Health Promotion in Okinawa (Japan) and Indonesia from the Perspective of Blue Zones and Healthy Longevity - Hokama, Naoki; Sato, Mayumi; Djaya, Andi Muhammad Fiqri Muslih; Tamura, Yuki; Imura, Kiyoko; Sugimoto, Hiroshi; Seto, Kiyoka (Faculty of Nursing, Universitas Hasanuddin, 2025)
In March 2024, I had the opportunity to visit the city of Loma Linda, California, USA, for training. Loma Linda is a green town with a population of about 25,000, where residents exhibit a high level of health consciousness, particularly in their diet. I learned that this area has been attracting attention since around 2000 as a so-called